Association between Exposures of Interest with Serum Lipopolysaccharide and Troponin Concentrations Based on Univariable Models‡ in 36 Client-owned Dogs with Untreated Myxomatous Mitral Valve Disease (MMVD). - Maria C. Jugan (18928389) (2025)
Association between Exposures of Interest with Serum Lipopolysaccharide and Troponin Concentrations Based on Univariable Models‡ in 36 Client-owned Dogs with Untreated Myxomatous Mitral Valve Disease (MMVD).